The rubber seed production in Sri Lanka. results of an islandwide survey - Seneviratna, P.; Witharana, L.P.P.; De Alwis, M.N. (Rubber Research Institute. Agalawatta, 1999)
Seed Production of rubber plantations in certain areas of Sri Lanka has gone down to very low levels affecting the quality of the planting material I.e.budded stump.An island wide survey was therefore conducted to gain soem knowledge on the quality and the quantity of the seeds produced on different clones in different climatic regions of Sri Lanka.the results confirmed that the regional effects most probably owing to climatic and weather factors are the main causes while the clonal effect was minimum.It was evident that the seed production in dry region is far more than the country's requirement for the production of budded stumps for annual repllanting programme.
Keywords: Agriculture; Hevea brasiliensis; Rubber; Seed production; Seed quality